Kinerja Bata Ekologis Berbasis Tanah Lokal pada Sistem Modular: Studi Kasus Sekolah Hikari - Asy Syaima Adam; Hilmi Dewani Fauziah; Safanisa Aurellia; Irfan Sabarilah Hasim; Utami Utami; Eggi Septianto; Fadilah Hasim (Universitas Sebelas Maret Surakarta, 2026)
Local Soil-Based Ecological Bricks Performance in a Modular System: A Case Study of Hikari SchoolThe construction industry contributes significantly to carbon emissions and material waste, thus necessitating more eco-friendly and efficient alternatives. This study aims to evaluate the performance of eco-bricks made from local soil in a modular system at Hikari School. The methodology employed is a descriptive qualitative approach using a case study design, involving literature review, field observations, documentation, and interviews. The results show that eco-bricks utilize local soil, are produced without firing, reduce cement requirements, and support an efficient and flexible interlocking system. Vertical voids serve as installation pathways, thermo-acoustic elements, and column spaces. Damage is generally influenced by user activity, humidity, and finishes, rather than structural failure of the material.